Functional Analysis of a Salicylate Hydroxylase in Sclerotinia sclerotiorum - Shengfei He; Kun Huang; Baoge Li; Guodong Lu; Airong Wang (Journal of Fungi, 2023)
Salicylic acid plays a crucial role during plant defense to Sclerotinia sclerotiorum. Some bacteria and a few fungi can produce salicylate hydroxylase to degrade SA to suppress plant defense and increase their virulence. But there has been no single salicylate hydroxylase in Sclerotinia sclerotiorum identified until now. In this study, we found that SS1G_02963 (SsShy1), among several predicted salicylate hydroxylases in S. sclerotiorum, was induced approximately 17.6-fold during infection, suggesting its potential role in virulence. SsShy1 could catalyze the conversion of SA to catechol when heterologous expression in E. coli. Moreover, overexpression of SsShy1 in Arabidopsis thaliana decreased the SA concentration and the resistance to S. sclerotiorum, confirming that SsShy1 is a salicylate hydroxylase. Deletion mutants of SsShy1 (∆Ssshy1) showed slower growth, less sclerotia production, more sensitivity to exogenous SA, and lower virulence to Brassica napus. The complemented strain with a functional SsShy1 gene recovered the wild-type phenotype. These results indicate that SsShy1 plays an important role in growth and sclerotia production of S. sclerotiorum, as well as the ability to metabolize SA affects the virulence of S. sclerotiorum.